CONCEPT OF DETECTION SYSTEM TO LOCALIZE INSIDE CLOSED AREA BY RADIO TOMOGRAPHIC IMAGING - Rymarczyk, Tomasz; Adamkiewicz, Przemysław; Szumowski, Jakub; Niderla, Konrad; Gołąbek, Łukasz; Sikora, Jan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
System for navigation and localization inside buildings will determine man's location in confined spaces with level of accuracy never yet achieved. System's operation will be mainly based on Bluetooth signals in accordance with the Beacon standard. A worldwide innovation will be the use of Radio Tomographic Imaging (RTI). This technology will enable tracking of moving objects by image reconstruction based on changes of electromagnetic field signal strength (RSS).